Corrosion behavior of Al-Si-Mg coated hot-press-forming steel. (1st May 2021) - Kim, Changkyu; Cho, Seongkoo; Yang, Wonseog; Karayan, Ahmad Ivan; Castaneda, Homero
Highlights: Small amount of Mg was added into the Al-Si coating for hot-dip-aluminizing (HDA) and hot-press-forming (HPF) processes. The added Mg was segregated toward the top-most layer during both HDA and HPF, but more segregation observable in HPF. The Mg segregation counteracted the inhibiting interdiffusion layer, resulted in thicker coating with and more compact coating surface. The Al-Si-Mg coating showed better corrosion resistance than the Al-Si coating, especially in early immersion period. Abstract: This study introduces enhanced corrosion performance of the Al-Si-Mg coated 22MnB5 boron steel. Structural changes of the coating after hot-dip-aluminizing and hot-press-forming processes with the presence of Mg included compacter surface with Mg segregation and thicker crack-free layer. Electrochemical corrosion tests indicated higher polarization resistance from the Al-Si-Mg sample compared to the reference Al-Si sample, especially in an early period of immersion. Such enhanced anti-corrosion performance can be attributed to the aforementioned structural changes and pore-filling effect of corrosion products. This study depicts that the Al-Si-Mg coating can be considered as another option for hot-press-forming steel by its enhanced barrier protection vs. Al-Si coating.